Comparison Analysis of Non Performing Loans and Performing Financing ( Case Study of BRI and Bank Muamalat ) - Ary Dean Amri; Alifah ,; Annisa .; Hayatun Nisaa; Helmalia Putri Tsalsabina (JOURNAL OF SHARIA ECONOMICS, 2023)
The global financial crisis that occurred several years ago has had a significant impact on the banking sector worldwide. One indicator that is often used to measure the financial health of a bank is the level of Non-Performing Loans (NPL) and Non-Performing Financing (NPF). NPL refers to credit that is not paid by the borrower within a certain period of time, while NPF refers to non-current financing in the context of Islamic banking. The purpose of this research is to analyze the comparison of NPL and NPF at Bank Muamalat and Bank BRI. The method used in this study is a quantitative approach by collecting secondary data from the annual financial statements of the banks concerned. The data collected includes NPL and NPF levels during the study period. The results of the analysis show that there are significant differences in the levels of NPL and NPF between Bank Muamalat and Bank BRI. Bank Muamalat has higher NPL and NPF levels compared to Bank BRI. Factors that can affect the NPL and NPF levels between the two banks include credit policies, borrower profiles, and recovery measures taken by the banks.